2012
DOI: 10.1038/oby.2011.233
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Increased BMI in Young Adult Women

Abstract: Food insecurity has been associated with weight status in children and adults although results have been mixed. We aimed to identify whether food insecurity was associated with BMI in young adults and whether this association differed by gender and was modified by food stamp use and the presence of children in the home. Cross-sectional data from Wave 4 (2007–2008) of the National Longitudinal Study of Adolescent Health were analyzed. Multiple linear regression was used to investigate the association between fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 29 publications
8
77
2
1
Order By: Relevance
“…This result is consistent with the findings of at least one other study based on NHANES data that found a significant association between intermediate-level food insecurity (e.g., marginal food security and low food security) and high LDL-C, high triglycerides/HDL-C ratio, and high triglycerides only among women (Tayie and Zizza, 2009). While reasons for these gender differences are not entirely clear, they are consistent with the findings from our own study as well as from previous studies showing that food insecurity is associated with obesity only among women (Dinour et al, 2007; Gooding et al, 2012; Townsend et al, 2001). It is possible that women experiencing food insecurity make different nutritional choices than men in the same situation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the findings of at least one other study based on NHANES data that found a significant association between intermediate-level food insecurity (e.g., marginal food security and low food security) and high LDL-C, high triglycerides/HDL-C ratio, and high triglycerides only among women (Tayie and Zizza, 2009). While reasons for these gender differences are not entirely clear, they are consistent with the findings from our own study as well as from previous studies showing that food insecurity is associated with obesity only among women (Dinour et al, 2007; Gooding et al, 2012; Townsend et al, 2001). It is possible that women experiencing food insecurity make different nutritional choices than men in the same situation.…”
Section: Discussionsupporting
confidence: 92%
“…Also, a paradoxical relationship between food insecurity and increased obesity has been observed in the U.S. adult population, especially among women (Dinour et al, 2007; Gooding et al, 2012; Holben and Pheley, 2006; Laraia et al, 2010; Townsend et al, 2001). It has been hypothesized that food insecurity predisposes individuals to chronic disease by inducing unhealthy dietary behaviors, such as reducing dietary variety and giving preference to a few low-cost, energy-dense, and nutritionally poor foods (Seligman and Schillinger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal and cross-sectional studies suggested that food insecure women are more likely to be overweight or obese 10,[31][32][33] ; however, research on the association between food insecurity and obesity has produced mixed results among men. 14 Although two studies found a positive association in men, 13,33 the majority of studies suggested no evidence for such a direct link.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies has treated poor health, anxiety, depression, and obesity as outcomes of food insecurity and found a positive association between food insecurity and health outcomes among adult women (Adams et al, 2003;Gooding et al, 2012;Heflin et al, 2005;Lee et al, 2012;Olson, 2005;Siefert et al, 2001;Tarasuk, 2001;Townsend et al, 2001;Whitaker et al, 2006). Further, research indicates that there is a bidirectional relationship between maternal depression and food insecurity among rural, low-come families (Huddleston-Casas et al, 2009).…”
Section: Maternal Poor Health and Risky Health Behaviorsmentioning
confidence: 85%